2016
DOI: 10.1021/acs.orglett.6b01947
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Dearomative Allylic Alkylation of Indoles with Alkynes To Synthesize Indolenines with C3-Quarternary Centers

Abstract: A palladium-catalyzed dearomative allylic alkylation of indoles with alkynes to construct indolenines with C3-quarternary centers was reported. The in situ formed arylallene intermediate omitted the need to install leaving groups on the allylic compounds and employ extra oxidants to oxidize the allylic C-H bonds. The reaction exhibited good functional group tolerance and high atom economy. Moreover, the reaction was further expanded to synthesize pyrroloindolines and furanoindolines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 65 publications
0
12
0
1
Order By: Relevance
“…In a concurrent study, Lin, Yao, and co‐workers reported the dearomatizing allylic alkylation of indoles with aryl propynes to furnish indolines bearing C3‐quaternary stereocenters. Again, carboxylic acid co‐catalysts were required as additives (Scheme ) …”
Section: Alkynes As Electrophilic π‐Allyl Precursorsmentioning
confidence: 99%
“…In a concurrent study, Lin, Yao, and co‐workers reported the dearomatizing allylic alkylation of indoles with aryl propynes to furnish indolines bearing C3‐quaternary stereocenters. Again, carboxylic acid co‐catalysts were required as additives (Scheme ) …”
Section: Alkynes As Electrophilic π‐Allyl Precursorsmentioning
confidence: 99%
“…The synthetic route to access 1 is shown in Scheme 3. From readily available 2bromo-6-hydroxybenzaldehyde (7), an initial Sonogashira coupling [15,16] with propyne was accomplished to afford 11 at a 69% yield. Initial attempts to form the isoquinoline scaffold from 10 were unsuccessful both via conversion of 10 into the corresponding tertbutylimine followed by a copper-catalyzed imino-annulation [17] or attempting a tandem imine formation and subsequent ethynyl-imino cyclization reaction with ammonia [18].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Tamaru ([Pd 0 ]/BEt 3 ), Trost ([Pd 0 ]/9‐BBN‐C 6 H 13 ), You ([Ru II ]/ p TsOH), You ([Ir I ]/Fe(OTf) 2 ) and Bisai ([Pd 0 /BEt 3 /KO t Bu]) documented very elegant methodologies (Figure ). Additionally, Pd‐mediated allylic C−H activations and site‐selective insertion into C−C triple bonds deserve particular mention as parallel methodologies in the indole allylative dearomatization realm.…”
Section: Figurementioning
confidence: 99%